Small Sample Analysis of Performance Measures in the Asymmetric Response Model - Pedersen, Christian S.; Satchell, Stephen E. (Journal of Financial and Quantitative Analysis, 2000)
Christian S. Pedersen, Stephen E. Satchell, Small Sample Analysis of Performance Measures in the Asymmetric Response Model, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 3 (Sep., 2000), pp. 425-450